Immune Thrombocytopenic Purpura Secondary to Carcinoma Tongue: A Rare Case Presentation - Moumana Das; Rimi Som Sengupta; Jeetendra Kumar JM; Sagnic Mandal; Anirban Ghosh (Bengal Physician Journal)
Immune thrombocytopenic purpura (ITP) secondary to carcinoma tongue, is a relatively rare manifestation. An association of ITP with lymphoproliferative disorder comprises about 30% of cases of secondary ITP. A clinical correlation between ITP and carcinoma tongue was never reported before. Case description: A 48-year-old female with infiltrating squamous cell carcinoma tongue was admitted with isolated severe thrombocytopenia, without signs of active bleeding. She was treated conservatively and discharged. Then again after 15 days, she was readmitted with thrombocytopenia. Bone marrow examination showed megakaryocytic hyperplasia with normal morphology of erythroid and myeloid series with no evidence of infiltration of bone marrow by tumor cells. Finally, the diagnosis of ITP related to carcinoma tongue was reached. Conclusion: Immune thrombocytopenic purpura is mostly primary but it can occur secondary to autoimmune disorders, infections, such as HIV, Hepatitis C, H. pylori, lymphoid neoplasms and occasionally solid tumors. This patient is an example of ITP secondary to a solid tumor with a clinical course concomitant to the course of carcinoma tongue. This case supports the relationship between carcinoma tongue and the immune disease.